2003
DOI: 10.1046/j.1445-6664.2003.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in physiological responses to NaCl between salt‐tolerant Sesbania rostrata Brem. & Oberm. and non‐tolerant Phaseolus vulgaris L.

Abstract: Sesbania rostrata ( S. rostrata) Brem. & Oberm., a member of the Fabaceae family, has been used as a promising halophytic plant to ameliorate soil salinity in north-east Thailand. To obtain information regarding the mechanism of salt tolerance, the physiological responses of S. rostrata to NaCl was compared with those of the salt-susceptible species, kidney bean ( Phaseolus vulgaris L. cv. Meal). Seedlings were grown hydroponically with 0, 50, 100 and 150 m  NaCl for 10 days and their effects on growth, chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 26 publications
1
14
0
1
Order By: Relevance
“…Seeds of S. rostrata and Phaseolus vulgaris L. cv. Meal were germinated at 25°C for 2 days in darkness and grown hydroponically as reported earlier ( Jungklang et al . 2003).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds of S. rostrata and Phaseolus vulgaris L. cv. Meal were germinated at 25°C for 2 days in darkness and grown hydroponically as reported earlier ( Jungklang et al . 2003).…”
Section: Methodsmentioning
confidence: 99%
“…1998). Our previous study ( Jungklang et al . 2003) suggested that salt tolerance of S. rostrata to NaCl was related to the plant's ability to translocate Na + and Cl – from roots to shoots and trap them in the shoot cells.…”
Section: Introductionmentioning
confidence: 97%
“…The ions of Na + have similar impact -their excess leads to disruptions in ionic balance in plants and limited intake of other ions that are crucial for proper plant growth [26]. Too high levels of Na + and Cl -ions result in such a significant change of chemical composition of soils solution that is disrupts also the intake of nutrients that are crucial for plants life, like magnesium, nitrogen and phosphorus [27][28][29]. The excess of sodium ions in soil solution is accompanied by calcium deficiency in plants, because as a result of ion exchange it may be removed from the environment of the roots.…”
Section: Discussionmentioning
confidence: 99%
“…There exists a differential pattern of accumulation and/or partitioning of Na + and Cl − in plants (Zhao et al 2002 ), and their effects on growth and leaf area (Maggio et al 2007 ). Nevertheless, the accumulation and partitioning of Na + and Cl − in salinity-treated plants can be genotype dependent (Jungklang et al 2003 ;Garg and Singla 2004 ). Na + and/or Cl − preferentially accumulates in roots over shoots via salt tolerance (salt exclusion) mechanism and thereby maintains a substantial potential for osmotic water uptake into the roots by restricting the spread of Na + to shoots (Chartzoulakis et al 2002 ;Aydi et al 2008 ).…”
Section: Effect Of Uv-b On Plants and Their Damage Control Mechanismsmentioning
confidence: 99%